SPED Hub a sustainable educational landscape for children with special needs - Cruel, Jouvykovi Ignaecia F.; Galingan, Zenaida C.; Dul-loog, Vic L. (Quezon City College of Architecture, University of the Philippines Diliman, 2016)
"But schools are where children first see their society at work, where they watch us act as much as they hear us speak" (Gelfland, 2010). Eventhough the level of awareness of both the government and the private sector in providing equal opportunities to children with spacial needs have considerably increased, the Philippines' learning environment setting has yet to cope up. The lack of landscapes that takes into consideration the needs and unique conditions of students under the Special Education (SPED) program is evident in the state of established SPED Centers today - where both private and public institutions are confined in a classroom basis learning and exploring the full potential of outdoor learning experience in a setting well-suited for them is yet to be known. The study aims to integrate various programs and therapies under SPED with the principles of community-based planning, and the numerous design strategies on constructing a sustainable educational facility, in order to create a balanced, holistic, and inclusive landscape design that can accommodate various activities suitable for students of wide range of cases. The landscape shall promote a learning environment that reconnects the user with nature and the community as a tool, among others, to their development. Also, it shall advocate a setting where daily interactions between the community and the students are encouraged through the involvement of the locals in planning, constructing, maintaining, and operating thus establishing mutual understanding and expanding people's perceptions on children and adults with special needs.
includes appendices
Thesis (Bachelor of Landscape Architecture) -- University of the Philippines Diliman